Proposta de uma métrica de avaliação para parque tecnológico sob a ótica de um sistema de inovação estruturante - Heringer, Benedita Hirene de França (2011)
Science Parks are environments that foster innovation. In this sense, they are tools that aim to turn knowledge into wealth. The organization of the park has to be specifically designed to comply with this specific mission. Thus, there is a need to create an environment conducive to innovative activity of organizations. A Science Park must have as its mission the structuring of the innovation system in order to provide support to companies it installed. The proposition of this thesis was to assess whether the Science Park of Sao José dos Campos fits the type of structuring park, able to: enter your activities in an open economy and an increasingly globalized; garner strong public support to subsidize their research and expand its facilities, facilitating access to knowledge partnerships between companies and universities, forming clusters of innovation, developing human resources to meet the demands of knowledge at the speed that the modern world requires. The case study aimed to verify its key feature as is defined by ABDI and ANPROTEC (2008) and what role does science parks in terms of changes to the system of knowledge generation and business innovation in an emerging economy like Brazil. It also proposes a metric for assessing the maturity of this key feature. The methodology used was a single case study as a research tool with a questionnaire with semi-structured, divided into six blocks common to all companies and four specific blocks for companies in the aeronautics sector, energy, health and sanitation. The results point to a park still in a consolidation phase with many challenges ahead, not even a park being able to meet the huge challenges of structural innovation, but it certainly moves in this direction.